دور التحليل اللساني لفاتحة سورة الأنبياء في تفسيرها - سعدية عمراني; سهام عون; لنده غدير إبراهيم; ناريمان شقعار; نجاة طعبلي (جامعة الوادي - University of Eloued, 2025)
الملخص: بعد هذه الدراسة المفيدة والممتعة من واحدة من سور القرآن الكريم، توصلنا إلى بعض النتائج والمتمثلة في دور التحليل اللساني في تفسير فاتحة سورة الأنبياء وهي من السور المكية، كما أن التحليل اللساني يهتم بدراسة النصوص من خلال التطبيق عليها وهي خمسة مستويات: صوتي، صرفي، نحوي، دلالي، ونصي وتهدف هذه الدراسة إلى إبراز دور التفسير، كما طبقت هذه المستويات على هذه الآية في الجانب التطبيقي فالمستوى الصوتي الذي يندرج ضمن أحكام لغوية صوتية، أما الصرفي غني بالمسائل الصرفية الموجودة في التفسير من بينها الأبنية الصرفية، والمستوى النحوي يعنى بفهم معاني القرآن الكريم، وهذا لارتباطه بالتفسير ارتباطا وثيقا، أما عن المستوى الدلالي يعنى بدراسة العلاقات الدلالية التي تهتم بالمعنى، وفي آخر هذه المستويات المستوى النصي الذي يقوم على الاتساق والانسجام من خلال الأدوات المستعملة والمتنوعة في النصوص. After this useful enjoyable study of one of the surahs of the Holy Qur'an, we reached some results,namely the role of linguistic analysis in interpreting the opening verse of Surat Al-Anbiya, which is one of the Meccan surahs.Linguistic analysis is concerned with studying texts through Application ,and there are five levels: phonetic,morphological,syntactic,semantic,and textual. This study aims to highlight the role of the practical aspect.The phonetic level falls within phonetic linguistic rules. The morphological level is rich in morphological issues found in interpretation,including morphological structures. The grammatical level is concerned whith understanding the meanings of the Holy Qur'an, due to its close connection to interpretation.The semantic level is concerned with studying the semantic relationships that concern meaning.At the last of these levels is the textual level , which is based on consistency and harmony through the various tools used in texts. _Linguistic analysis of the opening off the Surah of levels.
لسانيات عامة
Keywords: التحليل اللساني - سورة الأنبياء -التفسير; Analyse linguistique - Sourate Al-Anbiya - Interprétation